2008
DOI: 10.1111/j.1945-5100.2008.tb00608.x
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of cometary dust tracks in Stardust aerogel and laboratory calibrations

Abstract: Abstract-The cometary tray of the NASA Stardust spacecraft's aerogel collector was examined to study the dust captured during the 2004 flyby of comet 81P/Wild 2. An optical scan of the entire collector surface revealed 256 impact features in the aerogel (width >100 μm). Twenty aerogel blocks (out of a total of 132) were removed from the collector tray for a higher resolution optical scan and 186 tracks were observed (track length >50 μm and width >8 μm). The impact features were classified into three types bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
211
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 137 publications
(223 citation statements)
references
References 24 publications
12
211
0
Order By: Relevance
“…Type C tracks-these have bulbous cavities without a slender terminus. A detailed discussion of the frequency and morphology of each type is given in Burchell et al (2008). Here we note that type A comprised 65%, B 33%, and C 2% of all tracks.…”
Section: Tracks In Stardust Aerogelmentioning
confidence: 99%
See 3 more Smart Citations
“…Type C tracks-these have bulbous cavities without a slender terminus. A detailed discussion of the frequency and morphology of each type is given in Burchell et al (2008). Here we note that type A comprised 65%, B 33%, and C 2% of all tracks.…”
Section: Tracks In Stardust Aerogelmentioning
confidence: 99%
“…In the laboratory, projectiles with very different cohesive properties, composition and grain sizes reproduce the range of track morphologies as distinct classes (Hörz et al 1998;Burchell et al 2008). The Stardust aerogels contain the full range of these morphologies and their gradual transitions.…”
Section: Tracks In Stardust Aerogelmentioning
confidence: 99%
See 2 more Smart Citations
“…It has also been suggested that interstellar dust grains may consist primarily of such aggregate structures [6], [7], with a mixture of various chemical compositions and vacuum. It is now well accepted from the in situ measurements of comets and Stardust-returned samples of Comet Wild 2 that cometary dust consists of a mixture of compact particles and aggregates [8], [9], [10], [11], [12], etc.…”
Section: Introductionmentioning
confidence: 99%